The species of Notiobia Perty (Coleoptera: Carabidae: Harpalini) from Brazil - ARNDT,Erik (1998)
The new species Notiobia glabrata, N. maxima and N. pseudolimbipennis are described. A key to the 11 Notiobia (s.str.) species known from Brazil, data about the distribution of each species and taxonomical remarks are provided. Notiobia parilis Bates, 1878 is a junior synonym of N. nebrioides Perty, 1830, and Notiobia umbrata Bates, 1882 is a junior synonym of N. jlavicinctus Erichson, 1847. The Brazilian Notiobia species belong to at least three different species groups, each distributed from Brazil over the North-Western part of South America, Central America to Mexico.